2021
DOI: 10.1093/bjs/znab273
|View full text |Cite
|
Sign up to set email alerts
|

Completion pancreatectomy or a pancreas-preserving procedure during relaparotomy for pancreatic fistula after pancreatoduodenectomy: a multicentre cohort study and meta-analysis

Abstract: Background Despite the fact that primary percutaneous catheter drainage has become standard practice, some patients with pancreatic fistula after pancreatoduodenectomy ultimately undergo a relaparotomy. The aim of this study was to compare completion pancreatectomy with a pancreas-preserving procedure in patients undergoing relaparotomy for pancreatic fistula after pancreatoduodenectomy. Methods This retrospective cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 58 publications
1
23
0
Order By: Relevance
“…See Table 4 for the outcomes. In the present study, 21% of patients with POPF grade B/C underwent a rescue pancreatectomy, which is in line with the identified literature (6–30%) [ 9 , 22 , 24 , 27 , 32 ]. Whereas the need for rescue pancreatectomy has decreased over the years by improvement of minimally invasive management [ 12 ], the rescue pancreatectomy rate at Karolinska University Hospital did not decrease significantly.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…See Table 4 for the outcomes. In the present study, 21% of patients with POPF grade B/C underwent a rescue pancreatectomy, which is in line with the identified literature (6–30%) [ 9 , 22 , 24 , 27 , 32 ]. Whereas the need for rescue pancreatectomy has decreased over the years by improvement of minimally invasive management [ 12 ], the rescue pancreatectomy rate at Karolinska University Hospital did not decrease significantly.…”
Section: Discussionsupporting
confidence: 91%
“…In the PORSCH trial, still 8% of the patients who underwent a PD in the intervention group needed a relaparotomy. A retrospective analysis from the Dutch Pancreatic Cancer Group revealed that rescue pancreatectomy was associated with higher mortality in comparison to pancreas-preserving surgery, strengthened by the literature [ 9 ]. Furthermore, mortality was similar between simple surgical drainage and other pancreas-preserving surgical interventions, whereby clinical condition and additional intervention rates were similar [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, although few patients were included, 2 patients who underwent completion pancreatectomy experienced in-hospital mortality (100%). A recently published meta-analysis reported that a pancreas-preserving procedure seems preferable to completion pancreatectomy in patients in whom relaparotomy is deemed necessary for POPF after PD [ 21 ]. Emergency completion pancreatectomy is also a technically difficult procedure because of active bleeding, severe adhesions around the splenic vessels, and necrotized friable remnant pancreas and adjacent organs.…”
Section: Discussionmentioning
confidence: 99%